1984
DOI: 10.1128/mcb.4.7.1402
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of p53 gene expression by an insertion of Moloney murine leukemia virus-like DNA sequences.

Abstract: Analysis of Abelson murine leukemia virus-transformed L12 cells which lack the p53 cellular encoded tumor antigen revealed alterations in the p53-specific genomic DNA sequences. The active p53 gene, usually contained in a 16-kilobase EcoRI DNA fragment of p53 producer cells, went through major alterations leading to the appearance of a substantially larger 28.0-kilobase p53-specific EcoRI fragment. Detailed restriction enzyme analysis, with genomic probes spanning throughout the whole active p53 gene, indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 45 publications
4
80
1
Order By: Relevance
“…Moreover, point mutations in p73 may not be the only way to abrogate or compromise p73 function. For example, p53 structure and functions can be altered by conformational changes in the p53 protein, slicing abnormalities, viral protein binding, and upregulation of intrinsic proteins such as MDM-2 [29][30][31][32][33][34][35]. Thus the absence of p73 coding mutations does not exclude p73 from playing a role in AML.…”
Section: Mutation Of the P73 Genementioning
confidence: 99%
“…Moreover, point mutations in p73 may not be the only way to abrogate or compromise p73 function. For example, p53 structure and functions can be altered by conformational changes in the p53 protein, slicing abnormalities, viral protein binding, and upregulation of intrinsic proteins such as MDM-2 [29][30][31][32][33][34][35]. Thus the absence of p73 coding mutations does not exclude p73 from playing a role in AML.…”
Section: Mutation Of the P73 Genementioning
confidence: 99%
“…We found that introducing a functional p53 gene into L12 (Abelson murine leukemia virus-transformed cells that lack p53 [32,34] changed their phenotype, and instead of regressing tumors, they caused lethal tumors in the hosts (33). Our conclusion was that L12 cells, which express the abl oncogene but lack p53 expression, are only partially transformed, and that the expression of a completely transformed phenotype requires the concomitant expression of abl and p53.…”
mentioning
confidence: 71%
“…Heteroduplex analysis of the cloned human gene and the full-length human cDNA showed that it consists of about seven major exons. In the mouse there are two noncontiguous p53 genes (24,32,34,36), a principal active gene and a pseudogene, that map to different chromosomes (5,29). It is suggested therefore that in spite of the apparent resemblance between the mouse and human p53 proteins and the relatively conserved homology in their cDNA sequences (18), the structure of their p53 genes and their relative exon-intron localization seem to present unrelated patterns.…”
mentioning
confidence: 98%
“…For example, p53 structure and function can be altered by conformational changes in the p53 protein, splicing abnormalities, viral protein binding, and upregulation of intrinsic proteins such as MDM-2. 6,8,17,[38][39][40][41][42][43][44][45][46][47][48][49][50] Thus, the absence of p73 coding mutations does not exclude p73 from playing a role in AML.…”
Section: Discussionmentioning
confidence: 99%